PENGARUH SOLVABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN BUMN GRUP KARYA BIDANG JASA INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cahyaningsih, Febriana Arofani; Habibi, Azwar (Politeknik Negeri Lhokseumawe, 2025)
Abstract: The phenomenon of trouble here arose when four shares of BUMN work simultaneously crashed into the red zone in 2020. Erick Thohir, Minister of State Property Agency (BUMN), announced the collapse of four BUMN shares as a result of the COVID-19 pandemic, but what happened in order to reverse the situation in 2021 has increased the debt while the number of new contracts continues to decrease. In 2022, the compact BUMN issuer recorded an increase in revenue, but it hasn't been able to cure the sickness of burdened debt.The purpose of the research is to analyze the liquidity solvency and size of the company versus profitability either simultaneously or partially. The study aims to find out the impact of solvency, liquidity and size of the company on profitability of BUMN Infrastructure Services Working Group listed on the Indonesian Stock Exchange. This research includes quantitative research, Population in this research is 9 companies BUMN group of work in the field of infrastructure that is on the Indonesian stock exchange. The sampling technique in this study uses purposive samplings so the number of samples used in this research is 108 samples of triwulan financial statements of companies, but out of 108 examples of financial reports there are only 96 complete and testable financial reports. With regard to the measurement of the research instrument used in this study, namely solvency (Debt to Equity Ratio), liquidity (Current Ratio) and corporate size (Ln Total Asset), the data analysis technique used in the study is double linear regression analysis with the help of the SPSS 24 software tool. The results of the study showed that on the variable Solvency affected profitability with the test value obtained |thitung | ttable or sig 0.05 is |3,453 |1,994 or 0,0010,05, on the liquidity variable showed an influence on profitability by the value produced |the calculation |table or sig0.05 is 3,216 | 1,994, or 0,00205, and the size of the corporate variable indicated that there was no influence upon profitability at the calculable value | 0,05 is |81,42 |0,01,995, or 00,695. Solvency, Liquidity, and Size of the Company influence profitability with a calculated value Ftable or sig 0.05 that is 3,768 2,737 or 0,013 0,05.Keywords: Liquidity, Profitability, Solvency, and Company Size